Study on Settlement and Deformation of Urban Viaduct Caused by Subway Station Construction under Complicated Conditions - Cong-shuang Luo; Yi-hong Cheng; Zhe Bai; Tong Shen; Xu-Yang Wu; Qing-guo Wang (Advances in Civil Engineering)
With the rapid development of urbanization, the speed of constructing urban underground space and ground foundation engineering is accelerated. With the shortage of land resources, the distance between underground engineering and surface engineering is getting closer and closer, and the contradictions and problems between projects are becoming more and more serious. Based on the new subway station, this paper passes the existing urban viaduct in a short distance. The settlement and deformation of pile foundation and buildings caused by the excavation of the subway station is studied by using ROCSCIENCE software and site monitoring method. The potential risk sources around the station are pile foundations 18.5 m away, residential buildings 15 m away, storm water pipes 7.3 m away, and high-pressure gas pipes at 5.6 m. According to the construction requirements of pile foundation settlement deformation during metro station excavation, we set up construction standards. The settlement of the buildings and pipelines around the metro station should not exceed 3 mm, and the horizontal displacement should not exceed 2 mm. The diaphragm wall is adopted to surround the subway station, and the ground is reinforced by advanced grouting. The results show that, during the excavation of the foundation pit of the metro station, the ground and the building will have obvious settlement deformation and the depth of deformation can reach 9 mm, which is more than the allowable value. The settlement deformation of the ground and the surrounding buildings can be controlled within 3 mm by strengthening the foundation pit support and ground advance-grouting reinforcement. The control of construction deformation can meet the construction requirements.